2018
DOI: 10.1177/0149206318764296
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Governance and Corporate Financial Fraud in Transition Economies: Evidence From China

Abstract: How corporate governance mechanisms function in transition economies is a key topic for corporate governance researchers and policy makers. We propose that alternative governance mechanisms are in place to mitigate corporate fraudulent behaviors in the fluid state of transition economies where the establishment and enforcement of corporate governance legislation are presently insufficient. Drawing on the twin set of institutional logics—the institutional embeddedness logic and the institutional substitution lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 158 publications
3
93
0
9
Order By: Relevance
“…So, we included the ratio of misdemeanant's alters that also committed financial fraud, which equals the number of alters that committed financial fraud divided by the total number of alters. Finally, firms’ behaviors are embedded in and shaped by institutions (Yiu et al, 2018), so we controlled the misdemeanant's formal institutions with its province's marketization index. This index has been widely used in many studies to capture the qualities of the regional institutional environment (Shi, Sun, & Peng, 2012; Sun, Hu, & Hillman, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, we included the ratio of misdemeanant's alters that also committed financial fraud, which equals the number of alters that committed financial fraud divided by the total number of alters. Finally, firms’ behaviors are embedded in and shaped by institutions (Yiu et al, 2018), so we controlled the misdemeanant's formal institutions with its province's marketization index. This index has been widely used in many studies to capture the qualities of the regional institutional environment (Shi, Sun, & Peng, 2012; Sun, Hu, & Hillman, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zhang et al (2008) found that firms are more likely to manipulate earnings when decision makers are unable to achieve goals through legitimate means, while Mishina et al (2010) showed that high-performing firms are also more likely to engage in illegal activities due to decision makers’ loss aversion. Similarly, while Yiu, Wan, and Xu (2018) found that external governance as one type of informal institution can deter corporate financial fraud, Shi, Connelly, and Hoskisson (2017) found that external governance may lead to financial fraud due to high expectations from stakeholders. One reason accounting for this inconsistency may be that prior researchers seemingly adopt a static perspective on firm misconduct and overlook the interdependence between these acts.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Although most studies suggest that state ownership can be detrimental to effective corporate governance, a recent study (Yiu, Wan, & Xu, ) argues that “state ownership plays a strong governance role in firms” (p. 2696). This is because the state has a low level of information asymmetry with managers, facilitating monitoring of managers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Chinese legal decisions have allowed supervisors to walk away unscathed, even if they did not fulfil their roles satisfactorily. In financial fraud cases, members of the supervisory boards of listed companies should bear concrete administrative responsibility in the form of warnings and fines [44]. This was clearly borne out in the case of Shanxi Tian Neng Technology Co. Ltd (ST Ltd).…”
Section: Resultsmentioning
confidence: 99%